2005
DOI: 10.1007/s11120-004-7157-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of SulP, a nuclear-encoded chloroplast sulfate permease, in sulfate transport and H2evolution in Chlamydomonas reinhardtii

Abstract: Antisense technology was applied to the green alga Chlamydomonas reinhardtiito probe the function of a novel nuclear gene encoding a chloroplast-envelope localized sulfate permease (SulP; GenBank Accession Numbers AF467891 and AF481828). Analysis showed that antiSulP transformants are impaired in sulfate uptake, a consequence of repression in the SulP gene expression. Antisense antiSulP transformants exhibited a sulfur-deprivation phenotype, strong induction of arylsulfatase activity, and global induction of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(37 citation statements)
references
References 25 publications
2
34
0
1
Order By: Relevance
“…Four genes code for chloroplast envelopetargeted TM proteins (SulP and SulP2), a chloroplast stroma-targeted ATP-binding protein (Sabc), and a substrate (sulfate)-binding protein (Sbp) that is localized on the cytosolic side of the chloroplast envelope (309). Antisense mutagenesis of the SulP gene demonstrated a role in chloroplast sulfate uptake (67). FIG.…”
Section: Comparative Genomics Of Abc Systemsmentioning
confidence: 99%
“…Four genes code for chloroplast envelopetargeted TM proteins (SulP and SulP2), a chloroplast stroma-targeted ATP-binding protein (Sabc), and a substrate (sulfate)-binding protein (Sbp) that is localized on the cytosolic side of the chloroplast envelope (309). Antisense mutagenesis of the SulP gene demonstrated a role in chloroplast sulfate uptake (67). FIG.…”
Section: Comparative Genomics Of Abc Systemsmentioning
confidence: 99%
“…The link between SNRK2.1 kinase and repression of genes regulated by anoxic conditions is intriguing but could reflect an indirect impact of S deprivation on the physiological state of the cells. For example, a decrease in photosynthetic activity and an increase in HYD transcript accumulation and H 2 production was observed in Chlamydomonas transformants harboring antisense constructs of the chloroplast SO 4 22 permease (SULP1) grown in nutrient-replete medium (Chen et al, 2005). The authors suggested that the reduced permease activity in the transformants limited the supply of S to Phosphorous deprivation (ÀP) was used as internal control.…”
Section: Putrescine Biosynthesismentioning
confidence: 99%
“…In flooded crops, especially rice, the positive effect on production attributed to the presence of the freshwater fern Azolla and the cyanobacteria Anabaena azollae that develop a symbiotic relationship is well known. The annual fixation capacity of atmospheric nitrogen of this system is 350 -670 kg N fixed / ha, about 12 to 20 times higher than the fixing capacity presented by A. azollae isolated [89,90]. Wuang et al (2016) used the biomass of Spirulina platensis as an agricultural biofertilizer in different types of crops.…”
Section: Fertilizersmentioning
confidence: 88%